The Possibility of Sustainability Accounting Implementation in Village Owned Enterprise - Kurniawan, Putu Sukma; Sawarjuwono, Tjiptohadi (Universitas Swadaya Gunung Jati, 2023)
The purpose of this manuscript is to provide a new perspective on the possibility of implementing sustainability accounting in small business organizations, especially village-owned enterprise. We argue that even though small business organizations have limitations in organizational resources, they have a crucial role to play in implementing the concept of sustainability accounting in the business ecosystem. We developed the theoretical arguments based on the results of previous studies. We used the library research method to identify previous research in the context of sustainability accounting and small business organizations. We have found issues related to sustainability accounting and small business organizations. We also identify the issue and elaborate it in the theoretical arguments.